2015
DOI: 10.1038/ng.3417
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide association study confirms PNPLA3 and identifies TM6SF2 and MBOAT7 as risk loci for alcohol-related cirrhosis

Abstract: Alcohol misuse is the leading cause of cirrhosis and the second most common indication for liver transplantation in the Western world. We performed a genome-wide association study for alcohol-related cirrhosis in individuals of European descent (712 cases and 1,426 controls) with subsequent validation in two independent European cohorts (1,148 cases and 922 controls). We identified variants in the MBOAT7 (P = 1.03 × 10(-9)) and TM6SF2 (P = 7.89 × 10(-10)) genes as new risk loci and confirmed rs738409 in PNPLA3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
499
7
11

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 493 publications
(538 citation statements)
references
References 50 publications
21
499
7
11
Order By: Relevance
“…Interestingly, the previous in silico analyses have also suggested that MBOAT7 could trigger arachidonic acid release and thus promote HCC-linked phenotypes, such as inflammation and fibrogenesis [45,98]. This hypothesis is in line with recent studies reporting higher levels of proinflammatory metabolites of arachidonic acid in patients with NASH [99], just as was observed in the association between a variant in MBOAT7 and increased risk of liver damage in ALD/NAFLD patients [30,100]. Overall, these observations highlight that PNPLA3, and more generally lipid turnover, may impact liver carcinogenesis.…”
Section: Hypothetical Mechanisms For Liver Cancer Promotionsupporting
confidence: 79%
See 2 more Smart Citations
“…Interestingly, the previous in silico analyses have also suggested that MBOAT7 could trigger arachidonic acid release and thus promote HCC-linked phenotypes, such as inflammation and fibrogenesis [45,98]. This hypothesis is in line with recent studies reporting higher levels of proinflammatory metabolites of arachidonic acid in patients with NASH [99], just as was observed in the association between a variant in MBOAT7 and increased risk of liver damage in ALD/NAFLD patients [30,100]. Overall, these observations highlight that PNPLA3, and more generally lipid turnover, may impact liver carcinogenesis.…”
Section: Hypothetical Mechanisms For Liver Cancer Promotionsupporting
confidence: 79%
“…This association was subsequently replicated in several independent cohorts, mostly among individuals of European descent [26,27], and summarized in two metaanalyses [28,29] (Table 1). More recently, the first GWAS in ALD comparing 1426 heavy drinkers without liver injury to 712 patients with alcoholic cirrhosis, all of European descent, reported that PNPLA3, TM6SF2, and MBOAT7, three independent loci all involved in lipid metabolism, were significantly associated with a more severe phenotype [30]. Among them, variants in the PNPLA3 gene had the strongest signal with GWAS-significance.…”
Section: Alcoholic Liver Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…The diagnosis of alcohol-related cirrhosis was established as described previously [12], and based on a history of prolonged, sustained alcohol intake of a minimum of 40g/day, if female, and 60g/day, if male, and histological examination of liver tissue; or compatible historical, clinical, laboratory, radiological and endoscopic features. Patients were excluded if they had any other potential cause of liver injury, although a proportion of the participants were overweight.…”
Section: Patient Cohortsmentioning
confidence: 99%
“…Recently, variants in two further genes viz. rs58542926 in transmembrane 6 superfamily member 2 (TM6SF2) and rs641738 in membrane bound O-acyltransferase domain containing 7 (MBOAT7) were identified as risk factors for the development of alcohol-related cirrhosis in a genome-wide F o r P e e r R e v i e w association study (GWAS) [12]. Although a proportion of the cases included in the GWAS had developed HCC, the numbers were too small to allow for a meaningful subset analysis.…”
Section: Introductionmentioning
confidence: 99%